Darriwilian species of Histiodella (Conodonta) in the Argentine Precordillera - Mestre García, Ana Isabel; Heredia, Susana Emma (Alcheringa: An Australasian Journal of Palaeontology)
The Middle Ordovician successions in the Central Precordillera of Argentina are characterized by carbonate and fine mixed carbonate/ siliciclastic deposits. Two middle Darriwilian sections spanning the Eoplacognathus pseudoplanus to Eoplacognathus suecicus Zones were sampled for conodonts, among which were found species of Histiodella. We revised the biostratigraphical distribution of these species in the Middle Ordovician of the Precordillera. This study confirms that the Darriwilian species of Histiodella present in the Argentine Precordillera have a similar distribution to those of equivalent age in Newfoundland, South China and the Baltic region. On the other hand, the overlap in the ranges of H. holodentata and H. kristinae seems to be restricted to a fairly short interval in the upper part of the E. pseudoplanus Zone. We also propose that the FAD of H. kristinae Stouge is accurately positioned in the upper part of the E. pseudoplanus Zone; thus this species should not be used to define the base of the E. suecicus Zone in the Ordovician biozonation of the Argentine Precordillera. Fil: Mestre García, Ana Isabel. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - San Juan; Argentina. Universidad Nacional de San Juan. Facultad de Ingeniería. Instituto de Investigaciones Mineras; Argentina Fil: Heredia, Susana Emma. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - San Juan; Argentina. Universidad Nacional de San Juan. Facultad de Ingeniería. Instituto de Investigaciones Mineras; Argentina